Development of a Website for Publicizing the Multimedia Technology Program at Rajamangala University of Technology Isan, Surin Campus - Sanguansri, Sirawit; Pengkrajung, Thanakorn; Potisarn, Nawuttagorn; Yuenying, Winit (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
In the present era, effective curriculum management requires the utilization of modern technology to communicate efficiently with stakeholders. This research aims to develop and evaluate a website designed to publicize the Multimedia Technology Program at Rajamangala University of Technology Isan, Surin Campus, utilizing the ADDIE Model for game development. The sample was students at Rajamangala University of Technology Isan, Surin Campus, including 30 people. The research instruments were a questionnaire and a website quality assessment form. The collected data was analyzed by mean and standard deviation. The findings indicate that the developed website achieves modern aesthetics and ease of use, with appropriate use of colors and typography, enabling efficient information access. The content is clear, accurate, and reliable, organized in a user-friendly manner. Images used on the website are suitable and consistent with the content, enhancing the overall appeal and comprehension. The evaluation of the website designed found that the overall average was at a good level, with a mean of 4.24 and a standard deviation of 0.57. In conclusion, this research underscores the importance of good design, clear content, and appropriate imagery in creating an effective and user-friendly website. This will be beneficial for effective communication for course stakeholders.